Design of an internet of things based real-time monitoring system for retired patients - Vaclav Mach; Milan Adamek; Jiri Sevcik; Jan Valouch; Karla Barcova (Bulletin of Electrical Engineering and Informatics, 2021)
The main aim of this article is to design a monitoring center for collecting and evaluating the physiological function of retired patients in nursing homes. The system should be able to collect the information of body heat, heart rate, blood oxygen, orientation, and sleep time in the form of the little bracelet. The evaluating part of the system with the program can be placed into personal computer (PC) which can provide a user-friendly interface and easy managing. The program can display all needed information of the patient from previous days or months in the form of the graphs and the nursing person can have the view of the patient´s physiological health. The evaluation and the collection of the data from each patient are done only on the card and the computer is only a device for live-view and managing. In case of the power failure, the monitoring system will be still operating normally due to the uninterruptible power supply (UPS) in the form of the battery. It means that the system will operate even if the PC is powered off. The system also has several external communication interfaces like wireless fidelity (Wi-Fi), ethernet, and general packet radio service (GPRS) which provides an external connection.